Vaccine advice for food- and waterborne diseases. (2nd July 2019) - Brewer, Catherine
Abstract : It is common for travellers to experience severe disruption from becoming unwell with food- and waterborne diseases. Catherine Brewer looks at the diseases of hepatitis A, typhoid, polio and cholera and the administration of these vaccines